To the mind, heart, and will: Unravelling the appeals of Pope Francis’ pandemic homilies - Henry E. Lemana II (International Research Journal of Science, Technology, Education, and Management)
Homilies serve a crucial role in challenging, informing, directing, and inspiring congregations, especially during times of crisis. This study focuses on unravelling the appeals used by Pope Francis in 10 randomly selected homilies delivered amidst the COVID-19 pandemic. Findings reveal that Pope Francis utilizes three key appeals in his homilies. Firstly, he appeals to the mind by presenting ideas in a coherent and logical progression, incorporating examples and visual imagery to enhance comprehension. Secondly, he appeals to the heart by using literary devices, relatable language, and a deep understanding of the audience's needs to evoke emotions and provide comfort and encouragement. Lastly, he appeals to the will by urging his listeners to take action, promoting concrete steps to help others and alleviate suffering. Overall, Pope Francis employs these appeals to engage, inspire, and empower his audience in their spiritual journey. The study demonstrates that employing appeals, particularly in the context of a preacher like Pope Francis, is a persuasive and potent approach to engaging the intellect, stirring emotions, and inspiring action. Furthermore, this linguistic investigation highlights the significance of appeals in enhancing the profoundness of homilies, providing valuable insights into homiletics and linguistics. It establishes a foundation for further exploration at the intersection of religious discourse and linguistic analysis, offering the potential for new perspectives and methodologies in the examination of homilies.